7T: Physics, safety, and potential clinical applications. Issue 6 (3rd April 2017) - Kraff, Oliver; Quick, Harald H.
Abstract : With more than 60 installed magnetic resonance imaging (MRI) systems worldwide operating at a magnetic field strength of 7T or higher, ultrahigh‐field (UHF) MRI has been established as a platform for clinically oriented research in recent years. Profound technical and methodological developments have helped overcome the inherent physical challenges of UHF radiofrequency (RF) signal homogenization in the human body. The ongoing development of dedicated RF coil arrays was pivotal in realizing UHF body MRI, beyond mere brain imaging applications. Another precondition to clinical application of 7T MRI is the safety testing of implants and the establishment of safety concepts. Against this backdrop, 7T MRI and MR spectroscopy (MRS) recently have demonstrated capabilities and potentials for clinical diagnostics in a variety of studies. This article provides an overview of the immanent physical challenges of 7T UHF MRI and discusses recent technical solutions and safety concepts. Furthermore, recent clinically oriented studies are highlighted that span a broad application spectrum from 7T UHF brain to body MRI. Level of Evidence: 4 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1573–1589.